Extinction is Imminent for Mexico's Endemic Porpoise Unless Fishery Bycatch is Eliminated. Issue 5 (5th December 2016) - Taylor, Barbara L.; Rojas‐Bracho, Lorenzo; Moore, Jeffrey; Jaramillo‐Legorreta, Armando; Ver Hoef, Jay M.; Cardenas‐Hinojosa, Gustavo; Nieto‐Garcia, Edwyna; Barlow, Jay; Gerrodette, Tim; Tregenza, Nicholas; Thomas, Len; Hammond, Philip S.
Abstract: The number of Mexico's endemic porpoise, the vaquita ( Phocoena sinus ), is collapsing primarily due to bycatch in illegal gillnets set for totoaba ( Totoaba macdonaldi ), an endangered fish whose swim bladders are exported to China. Previous research estimated that vaquitas declined from about 567 to 245 individuals between 1997 and 2008. Acoustic monitoring between 2011 and 2015 showed a decline of 34%/year. Here, we combine visual line transect and passive acoustic data collected simultaneously in a robust spatial analysis to estimate that only 59 (95% Bayesian Credible Interval [CRI] 22–145) vaquita remained as of autumn 2015, a decrease since 1997 of 92% (95% CRI 80–97%). Risk analysis suggests that if the current, temporary gillnet ban is maintained and effectively enforced, vaquitas could recover to 2008 population levels by 2050. Otherwise, the species is likely to be extinct within a decade.